Transvaginal Sonographic Assessment Following Cervical Pessary Placement for Preterm Birth Prevention - Schnettler, William; Manoharan, Shwetha; Smith, Kate (American Journal of Perinatology Reports, 2022)
Background Transvaginal sonographic cervical length assessment identifies pregnant women at risk for preterm birth, and the subsequent placement of a cervical pessary may reduce this risk. The mechanism of action remains uncertain, and postplacement transvaginal sonography may provide further insight into the controversial efficacy of this therapy.Objective To identify any pre- or postplacement sonographic findings associated with preterm delivery following cervical pessary insertion among at-risk women.Materials and Methods This retrospective cohort study utilized electronic medical record and imaging review of all women identified within a large tertiary care health system having undergone cervical pessary placement for preterm birth risk reduction and subsequently delivered between January 2013 (the adoption of this therapeutic option in our system) and March 2017. Indications for cervical pessary placement were guided by maternal–fetal medicine consultation and required a functional cervical length measurement on transvaginal sonography of 25 mm or less. Criteria for initial transvaginal cervical assessment included obstetric history, multiple gestation, and current concern on transabdominal imaging for cervical shortening. All pre- and postplacement transvaginal sonographic measurements were determined for study purposes by re-review of each patient's images by a single author blinded to outcome.Results A total of 88 women were identified as having undergone cervical pessary placement for preterm birth prevention, and 52 yielded complete delivery and imaging data for inclusion. As expected, this was a high-risk population with 51.9% carrying multiple gestations, 32.7% with a history of prior preterm birth, and 11.6% with a history of cervical conization. Although previously hypothesized to represent the mechanism of action, neither the change in uterocervical or intracervical angle was associated with gestational age at delivery. Alternatively, preplacement imaging measurements of cervical funneling, anterior cervical length, and cervical diameter were significantly associated with appropriate pessary placement and decreased preterm birth. Forty-two subjects (80.8%) demonstrated both the anterior and posterior aspects of the cervix within the pessary (appropriate placement) and 95.2% of these subjects demonstrated cervical funneling on initial imaging compared with 25% of those with inappropriate placement (p = 0.002). Anterior cervical length less than 20 mm and cervical diameter less than 33 mm were associated with preterm delivery less than 28 weeks (16.7 vs. 0%, p = 0.039), and anterior cervical length less than 20 mm was associated with preterm delivery less than 32 weeks (41.7 vs. 10.7%, p = 0.025). Cervical diameter less than 33 mm correlated with an “inappropriately placed” pessary among 83.3% in comparison to 48.7% (p = 0.048) of women with a cervical diameter less than 33 mm. Significant associations were noted between postplacement functional cervical length measurements and preplacement anterior cervical length (p = 0.001) and cervical diameter (p = 0.012).Conclusion Contrary to current thinking, no significant changes in uterocervical and intracervical angle following cervical pessary placement were identified. However, preplacement sonographic measurement of funneling, anterior cervical length, and cervical diameter are predictive of appropriate pessary placement and extreme preterm birth. These may represent markers for candidacy of cervical pessary placement. Postplacement transvaginal sonography represents an important tool to assess potential efficacy of this therapeutic modality, and further investigation of these factors is warranted.
Keywords: preterm birth; cervical pessary; uterocervical angle; intracervical angle; cervical length; funneling; sonography; ultrasound